The impact of Strategic planning on hospital employees' job satisfaction: A case study - Ali Mohammad Mosadeghrad; Amin Ebneshahidi; Nazafarin Abdolmohammadi (Kerman University of Medical Sciences, 2017)
Background & Objectives: Hospital staff's job satisfaction has a significant role in improving the quality of hospital productivity. This study aimed to examine the impact of strategic planning on hospital staff's job satisfaction. Methods: This participatory action research was carried out in a selected private hospital in Isfahan/ Iran during 2012-2014. The hospital strategic plan, with a goal for improving job satisfaction was designed and implemented. Employees' job satisfaction was measured before and after implementing the strategic plan through 9-item Job Satisfaction Questionnaire. Data were analyzed through SPSS22 software package. Results: The rate of subjects' job satisfaction in 2012 was approximately 58.6%. The highest satisfaction rate was found for the nature of job and job and coworkers' needs and the lowest was obtained for salary, job promotion, work conditions and job security. Employees' job satisfaction increased to 64.7% in 2014 (10.1% improvement). Employees' tendency for job quit decreased by 61.4% (from 42.2% in 2012 to 16.3% in 2014). Strategic plan had the most impact on dimensions of job promotion, management and supervision, coworkers and salary. Conclusion: Adequate designing and implementation of a strategic plan can improve job satisfaction of employees and reduces their tendency for job quit. Keywords: Strategic planning, Employees, Job satisfaction, Hospital, Case study Citation: Mosadeghrad AM, Ebneshahidi A, Abdolmohammadi N. The Impact of Strategic Planning on Job Satisfaction among Hospital Staff: a case study. Journal of Health Based Research 2017; 3(2): 99-114.